Historical ecology and archaeology in the Galápagos Islands : a legacy of human occupation - Stahl, Peter W.; Astudillo, Fernando J.; Jamieson, Ross W. (Ross William), 1966-; Quiroga, Diego; Delgado, Florencio (Society and ecology in island and coastal archaeology., 2020)
The Galápagos Islands are one of the world's premiere nature attractions, home to unique ecosystems widely thought to be untouched and pristine. This volume reveals that the archipelago is not as isolated as many imagine, examining how centuries of human occupation have transformed its landscape.